Maternal pre-pregnancy weight and twins' temperament. (20th May 2019) - Tore, Elena C.; Antoniou, Evangelia E.; Reed, Keith; Southwood, Taunton R.; Smits, Luc; McCleery, Joseph P.; Zeegers, Maurice P.
Abstract: Maternal pre-pregnancy weight has been related with young singletons' cognitive and behavioral development, but it is not clear if it has an effect on temperament. We used a twin cohort to evaluate the association between maternal pre-pregnancy body mass index (BMI) and infants' temperament. The mothers of 834 twins answered questions regarding their pre-pregnancy BMI and their 0- to 18-month-old children's temperament using the Revised Infant Behavior Questionnaire. Three temperamental dimensions were examined: activity level, distress to limitation and duration of orienting. The relationship between maternal pre-pregnancy BMI and each temperamental component was investigated by means of multilevel mixed-effects linear regression analysis. We found no clear evidence of an association of maternal pre-pregnancy BMI with twins' temperament. The development of temperament is influenced by a large number of factors, probably different from those influencing children's emotional and behavioral development.